Techniques for rapid extraction of ingested food from wildfowl viscera - Pollard, D F W (Wildfowl, 1967)
Details of equipment and application are given for two methods for sampling wildfowl viscera The first method, suitable for use on grazing species, relies on dry extraction from the oesophagus and proventriculus by means of a self-opening crook. The second method, employed for extraction from seed and animal feeders, involves a simple water pump, with which food is washed from the gullet. The main advantages of these methods, which together should permit analysis of most species of wildfowl, are that it is unnecessary to dissect or disfigure the carcass in any way, and that a large number of birds may be treated in a short period.